(untitled) (FAVE Sección Ciencias Veterinarias, 2017)
The antibacterial activity of serum of bovine and buffaloes was evaluated in vitro indirectly by two immunohemolysis assays: (i) an unsensitized rabbit blood cells hemolysis-hemagglutination assay and (ii) and a hemolytic-kinetic of unsensitized rabbit blood cells in function of increasing serum concentrations. The serum bactericidal activity was evaluated in vitro by quantifying the reduction of the development of an Escherichia coli inoculum in a culture medium enriched with serum of both species. In the hemolysis-hemagglutination assay, the máximum haemolysis was observed until a 1:16 serum dilution for both species. The highest percentage of hemolysis was obtained with buffalo serum (84.7 ± 9.71%) with respect to bovine serum (71.0 ± 5.05%). However, no differences were found in the serum dilutions necessary to obtain 50% of the total hemolysis, being these 10.2 ± 2.48 for the serum of cattle and 11.8 ± 2.18 for the serum of buffalo. Buffalo serum reduced bacterial growth by 69.8% compared to 47.2% obtained by bovine serum. Despite these results, additional studies will be needed to corroborate these findings in vivo